Contextual information management: An example of independent-checking in the review of laboratory-based bloodstain pattern analysis. Issue 3 (May 2018) - Osborne, Nikola K.P.; Taylor, Michael C.
Abstract: This article describes a New Zealand forensic agency's contextual information management protocol for bloodstain pattern evidence examined in the laboratory. In an effort to create a protocol that would have minimal impact on current work-flow, while still effectively removing task-irrelevant contextual information, the protocol was designed following an in-depth consultation with management and forensic staff. The resulting design was for a protocol of independent-checking (i.e. blind peer-review ) where the checker's interpretation of the evidence is conducted in the absence of case information and the original examiner's notes or interpretation(s). At the conclusion of a ten-case trial period, there was widespread agreement that the protocol had minimal impact on the number of people required, the cost, or the time to complete an item examination. The agency is now looking to adopt the protocol into standard operating procedures and in some cases the protocol has been extended to cover other laboratory-based examinations (e.g. fabric damage, shoeprint examination, and physical fits). The protocol developed during this trial provides a useful example for agencies seeking to adopt contextual information management into their workflow. Highlights: The development and trial of a blinded peer-review procedure in laboratory-based BPA Item re-assessed by examiner blind to case circumstances and original opinion Simple and practical way to manage contextual information as a way to reduce bias Example for other agencies who wish to adopt context management procedures Suitable for other disciplines; e.g. shoeprint, fabric damage, physical fits